Pengaruh Brand Image, Kualitas Produk dan Promosi Terhadap Keputusan Pembelian (Studi Kasus pada Pelanggan PT. Propan Raya) - Agustinus Yanuar Budhi Heriyanto; Ahmad Rojikun; Fery Hernaningsih (eCo-Buss, 2021)
The reason for this study is that the competition among paint manufacturers is very fierce, so PT Propan Raya feels it is necessary to maintain and maintain the continuity of its business. Several new products flooded the market, giving buyers more choice. As a result of this change, customers have become increasingly careful when choosing and deciding on any product on the market. Therefore, If PT. Propan Raya can maintain its brand image, product quality, and promotion strategy, Propan Raya must consider increasing its market share. Many internal and external problems still need to be resolved at this time, for example, the brand image that customers do not fully understand, the quality of new products that do not support their quality, and an ineffective advertising system. This study examines the influence of brand image, product quality, and advertising on purchasing decisions (for example, customer PT Propan Raya). The independent variables in this study are brand image, high-quality products, and advertising. This is a purchase decision made by a PT customer. Propane belt. The data collection method is used by sending questionnaires directly to PT. Propane Eid al-Fitr customers use the propane brand in Timur Jakarta. The analysis method used in this study is based on the data of 100 interviewed customers, using the coefficient of determination analysis, multiple regression analysis Fest and SPSS 24.00 ttest version. It can be seen from the t-test results that the brand image t value is 2080, the product quality t value is 8052, and the advertising t value is 3.255, which are all greater than the t in Table 1688. This indicates that brand image, product quality, and advertising may have a positive impact on the purchase decision of PT. Propan Raya customers. Fcount> Ftable or 31.004> 2.87 or significance level (signal) 0.000 The adjusted definition shows that the influence of brand image, product quality, and advertising on public transportation customers’ purchasing decisions is 69.8%. In this study, the adjusted R2 value is 69.8%, which means that the dependent variable of PT Propan Raya’s customers may be different. We can use 69.8% of the model to explain using explanatory variables, and the remaining 30.2% is used for other variables besides independent variables, namely the contribution of brand image, quality, and product promotion; variables other than brand image, product quality, and advertising account for 69.8% The remaining 30.2%